Quantitative intracellular flux modeling and applications in biotherapeutic development and production using CHO cell cultures. Issue 12 (11th September 2017) - Huang, Zhuangrong; Lee, Dong‐Yup; Yoon, Seongkyu
Abstract: Chinese hamster ovary (CHO) cells have been widely used for producing many recombinant therapeutic proteins. Constraint‐based modeling, such as flux balance analysis (FBA) and metabolic flux analysis (MFA), has been developing rapidly for the quantification of intracellular metabolic flux distribution at a systematic level. Such methods would produce detailed maps of flows through metabolic networks, which contribute significantly to better understanding of metabolism in cells. Although these approaches have been extensively established in microbial systems, their application to mammalian cells is sparse. This review brings together the recent development of constraint‐based models and their applications in CHO cells. The further development of constraint‐based modeling approaches driven by multi‐omics datasets is discussed, and a framework of potential modeling application in cell culture engineering is proposed. Improved cell culture system understanding will enable robust developments in cell line and bioprocess engineering thus accelerating consistent process quality control in biopharmaceutical manufacturing. Abstract : The authors have reviewed the recent development of constraint‐based metabolic models and applications of models to CHO cell culture including media formation, feed strategy development, bioprocess control optimization, and cell line engineering. The review discusses the progress made in integrating constraint‐based models with multi‐omics datasets, and proposes a framework of further using these modeling approaches in CHO cells in the near future.